IMPLEMENTASI E-COMMERCE SEBAGAI MEDIA PENJUALAN ONLINE PADA KELOMPOK MENTARI - Imansyah, Fitri; Sujana, Ivan; Pragestu, Steven (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
Sungai Kupah Village, known for its natural beauty and local wisdom-filled rural community life, faces significant challenges in developing its local economy. One of the prominent local potentials is the production of shrimp sticks by a local community group, Kelompok Mentari. This group has focused its efforts on the shrimp stick business but faces major challenges in market access and product visibility. This study aims to develop a web-based e-commerce system that can assist Kelompok Mentari in marketing and selling their products online. Data collection was conducted through interviews, literature studies, and observations. The needs analysis, using the Rapid Application Development (RAD) approach, identified admin and buyers as actors in the system being built. The development process involved designing and refining prototypes based on user feedback, followed by the execution phase, which included scripting and determining the platforms, hardware, and software used. The system was tested using black box and user acceptance testing (UAT) methods to ensure feasibility and user needs compliance. The results show that the e-commerce system built can facilitate Kelompok Mentari in marketing and selling products online effectively. Every ordering process, from product management to sales report printing, runs smoothly. The system obtained a UAT score of 95% based on the Likert’s Summated Rating (LSR) scale, indicating that the system successfully meets the needs of Kelompok Mentari.